PENERAPAN SANKSI PIDANA TERHADAP ANAK SEBAGAI PERANTARA JUAL BELI NARKOTIKA BERDASARKAN UU NO 35 TAHUN 2009 (STUDI PUTUSAN 05/PID.SUS-ANAK/2015) - Novita Lailatul Fauziah; Wenny Megawati (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2024)
ABSTRACT The methodology approach used in this study is normative legal analysis. Legal provisions for safeguarding children's rights throughout the judicial proceedings are applied from the investigative stage, inquiry, prosecution, court examination, to the execution of court judgments. Throughout the legal process, the protection of children's rights must adhere to the relevant legal regulations and, consequently, should be consistently executed by the parties participating in addressing juvenile delinquency issues, as stipulated in Law No. 11 of 2012 concerning the Juvenile Criminal Justice System.